TRANSFORMATIONAL LEADERSHIP TRAINING FOR CHURCH LEADERS: A COMMUNITY ENGAGEMENT PROGRAM IN SALATIGA - Purwanto, Edi (Jurnal Pengabdian dan Kewirausahaan, 2026)
Rapid social transformation requires religious organizations to develop adaptive and visionary leadership capable of empowering communities sustainably. Church leaders play a strategic role not only in nurturing the spiritual life of congregations but also in strengthening the social contributions of churches within society. However, many church leaders have limited access to structured leadership training that can enhance their leadership capacity in responding to evolving social challenges. Therefore, this community engagement program aimed to strengthen the leadership capacity of church leaders through transformational leadership training. The training program was conducted in Salatiga, Central Java, Indonesia, in collaboration with GPIAI Salatiga as the partner. The program was held over two days and involved more than 80 church leaders and religious community leaders representing various churches and houses of worship in Salatiga and surrounding areas. The program adopted a participatory training approach consisting of lectures, group discussions, leadership reflection sessions, and training evaluations. The training materials focused on transformational leadership principles, development of a shared ministry vision, innovation in church ministry, and strategies for empowering congregational members in community service. The results indicate that the training significantly improved participants’ understanding of transformational leadership concepts and their application in church ministry. In addition, the program facilitated the development of collaborative networks among church leaders from different congregations and denominations in Salatiga. The findings demonstrate that leadership training can serve as an effective strategy for strengthening the capacity of religious community leaders to develop innovative, collaborative, and socially impactful ministry initiatives.